Verifying and reporting Fast Radio Bursts. Issue 2 (3rd September 2018) - Foster, Griffin; Karastergiou, Aris; Geyer, Marisa; Surnis, Mayuresh; Golpayegani, Golnoosh; Lee, Kejia; Lorimer, Duncan; Price, Danny C; Rajwade, Kaustubh
ABSTRACT: Fast Radio Bursts (FRBs) are a class of short-duration transients at radio wavelengths with inferred astrophysical origin. The prototypical FRB is a broadband signal that occurs over the extent of the receiver frequency range, is narrow in time, and is highly dispersed, following a ν −2 relation. However, some FRBs appear band-limited, and show apparent scintillation, complex frequency-dependent structure, or multi-component pulse shapes. While there is sufficient evidence that FRBs are indeed astrophysical, their one-off nature necessitates extra scrutiny when reporting a detection as bona fide and not a false positive. Currently, there is no formal validation framework for FRBs, rather a set of community practices. In this article, we discuss potential sources of false positives, and suggest a framework in which FRB-like events can be evaluated as real or otherwise. We present examples of false-positive events in data from the Arecibo, LOFAR, and Nanshan telescopes, which while FRB-like, are found to be due to instrumental variations, noise, and radio-frequency interference. Differentiating these false-positive detections from astrophysical events requires knowledge and tests beyond thresholded single-pulse detection. We discuss post-detection analyses, verification tests, and data sets which should be provided when reporting an FRB detection.